Endecous apterus: A new species of cave cricket from northeast Brazil, with comments on the use of subterranean habitats by Luzarinae crickets (Orthoptera: Grylloidea: Phalangopsidae: Luzarinae) - Souza-Dias, Pedro G.b.; Bolfarini, Márcio P.; Nihei, Silvio S.; de Mello, Francisco A.g. (Zootaxa, 2014)
In this study we describe the first apterous species of Endecous Saussure (1878), collected in two caves at Ituaçu, Bahia State, Brazil. In Brazil, Endecous is the most widespread cricket in hypogean environments and its species can colonize caves and inhabit the entrance and the aphotic zones; Endecous species can also be found in the litter, rock gullies, crevices, burrows, and any natural cavities. The use of subterranean habitat by Endecous crickets and its related genera are discussed.